2012
DOI: 10.1128/aem.07034-11
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Functionality of Mating Type Genes in the Supposedly Asexual Filamentous Fungus Aspergillus oryzae

Abstract: ABSTRACTThe potential for sexual reproduction inAspergillus oryzaewas assessed by investigating the presence and functionality ofMATgenes. Previous genome studies had identified aMAT1-1gene in the reference strain RIB40. We now report the existence of a complementaryMAT1-2gene and the sequencing of an idiomorphic region from Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…SLA (AMSELEM et al 2011;ARONSTEIN et al 2007;WADA et al 2012;WILKEN et al 2014) and APC (CONDE-FERRAEZ et al 2007;COZIJNSEN and HOWLETT 2003;WAALWIJK et al 2002;WILKEN et al 2014), in particular, have been described as MAT flanking genes in various species.…”
Section: Discussionmentioning
confidence: 99%
“…SLA (AMSELEM et al 2011;ARONSTEIN et al 2007;WADA et al 2012;WILKEN et al 2014) and APC (CONDE-FERRAEZ et al 2007;COZIJNSEN and HOWLETT 2003;WAALWIJK et al 2002;WILKEN et al 2014), in particular, have been described as MAT flanking genes in various species.…”
Section: Discussionmentioning
confidence: 99%
“…Gene targeting has advantages over random mutagenesis, particularly in introducing multiple desired changes in organisms where genetic crosses cannot be undertaken due to the lack of a sexual cycle. Even though functional mating type genes were recently identified in A. oryzae (26), because production strains have a range of lesions in their genomes, molecular rather than meiotic approaches will still be preferable to maintain the overall phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…3B). Other microarray studies have also demonstrated that MAT genes have a wide-ranging effect on fungal gene expression (26,(29)(30)(31).…”
Section: Mat1-1-1 Gene Controls Hyphal Morphology Conidiation and Pmentioning
confidence: 99%